2018
DOI: 10.1155/2018/8687108
|View full text |Cite
|
Sign up to set email alerts
|

Seepage Law of Injected Water in the Coal Seam to Prevent Rock Burst Based on Coal and Rock System Energy

Abstract: Rock burst is one of the typical dynamic disasters in coal mining. In order to reveal the mechanism of rock burst from the energy view point, the relationships between the maximum, minimum, and intermediate principal stresses and the concentration coefficients of the gravity stress k1, k2, and k3 are determined through the geostress measurement combined with engineering practice of coal mining. The coal and rock system model based on the tectonic stress is established. The relationship between energy and scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Coal and rock mass buried in deep is subjected to a complex geological environment with the depletion of shallow resources and the increase of coal mining depth [1,2]. Coal mass with great stored elastic energy may be subjected to strong impact loading when it is disturbed by mining operations, such as uncovering coal seam from rock mass, engineering blasting, roadway excavation, nearby coal seam mining, resulting in serious mine dynamic disasters such as rockburst, coal and gas outburst accompanyed with a large amount of released energy [3][4][5][6][7][8][9]. ese disasters may lead to great property losses and casualties.…”
Section: Introductionmentioning
confidence: 99%
“…Coal and rock mass buried in deep is subjected to a complex geological environment with the depletion of shallow resources and the increase of coal mining depth [1,2]. Coal mass with great stored elastic energy may be subjected to strong impact loading when it is disturbed by mining operations, such as uncovering coal seam from rock mass, engineering blasting, roadway excavation, nearby coal seam mining, resulting in serious mine dynamic disasters such as rockburst, coal and gas outburst accompanyed with a large amount of released energy [3][4][5][6][7][8][9]. ese disasters may lead to great property losses and casualties.…”
Section: Introductionmentioning
confidence: 99%
“…e occurrence mechanisms of the two are similar and they are difficult to be predicted [1][2][3][4]. e research on the mechanism of rock burst has always been an unsolved scientific problem that has been discussed for a long time in the fields of mining engineering and rock mechanics [5][6][7][8][9][10]. e application of CT scanning, 3D printing, big data, cloud computing, Internet of things, and other emerging technologies in the study of coal mine rock burst has become a hot topic in mining research [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al considered the effects of depth on the in situ stress environment and physical properties of coal and conducted triaxial compression experiments on 128 coal samples that were on this basis, showing that, with increasing depth, the elastic energy and dissipated energy increase more rapidly [12]. Lan et al established the coal and rock system model based on the tectonic stress and showed that the trend of released energy of damaged coal has good consistency with the variation of permeability, and water injection can reduce the stress concentration and energy concentration of the rock burst system [13]. Feng et al studied the relationship between stress-strain, uniaxial compressive strength, displacement rate, loading rate, fractal dimension, and energy dissipation rate through static loads and dynamic loads experiment [14].…”
Section: Introductionmentioning
confidence: 99%